Sulforaphane Promotes Adipocyte Thermogenesis: Molecular Insights, Anti-Obesity Potential, and Future Perspective - Widayanti, Iftitan Setya; Noer, Etika Ratna; Fulyani, Faizah (Faculty of Medicine, Universitas Diponegoro, 2025)
Over the past five decades, the increasing incidence of obesity has sparked considerable interest in nutraceuticals as promising natural alternatives for effective weight management and metabolic health improvement. Sulforaphane (SFN), an isothiocyanate abundant in cruciferous vegetables, has gained attention for its potential in obesity management, particularly by promoting the browning of white adipose tissue (WAT) and transforming it into energy-burning fat. While its potential is significant, the underlying molecular mechanisms are complex and require a comprehensive synthesis. Therefore, this review explores sulforaphane (SFN) as a potential nutraceutical alternative by examining the scientific evidence of its anti obesity effects, focusing on its ability to activate multiple signalling pathways, including Nuclear Factor Erythroid 2-related factor 2 (Nrf2), AMP-activated protein kinase (AMPK), and sirtuin 1 (SIRT1), as well as upregulation of uncoupling protein 1 (UCP1). These are the key pathways in mitochondrial biogenesis, lipid metabolism, and thermogenesis. Additionally, SFN can mitigate oxidative stress and modulate inflammatory responses, further contributing to improved metabolic function and energy expenditure. While much of the research on SFN has focused on its effects on mature cruciferous vegetables, current research increasingly directs attention to microgreens, which contain significantly higher concentrations of bioactive compounds, including SFN. This review highlights SFN’s molecular mechanisms underlying its role in the context of obesity, specifically its effects on WAT browning, metabolic regulation, and thermogenesis. We also explored the potential of microgreen-derived SFN as a promising nutraceutical for obesity intervention and metabolic regulation, highlighting the novel bioactive chemical and biological properties of these plants.